2018
DOI: 10.2514/1.j056961
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Transverse Gusts Using Pitching, Plunging, and Surging Airfoil Motions

Abstract: Three model-motions were developed to replicate the aerodynamic response of a transverse gust. These motions included a pure-plunging and two three degree-of-freedom motions that approximated the angle-of-attack distribution produced by the gust. Using inviscid models and viscous flow simulations, the response of the gust and model-motions were compared as a function of the non-dimensional reduced frequency. The inviscid model was found to overestimate the influence of the rotational added-mass in the three de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
(22 reference statements)
2
9
0
Order By: Relevance
“…For instance, authors have reported numerical and experimental results for periodic longitudinal gusts [4,5], transient localized transverse gusts [6], transient plunge maneuvers [7][8][9] and for vortical gusts [10,11], where the gust is induced by a passing vortex over the airfoil. The latter differs with respect to the others in that the gust intensity (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, authors have reported numerical and experimental results for periodic longitudinal gusts [4,5], transient localized transverse gusts [6], transient plunge maneuvers [7][8][9] and for vortical gusts [10,11], where the gust is induced by a passing vortex over the airfoil. The latter differs with respect to the others in that the gust intensity (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The similitude between transverse localized gusts and plunge/pitch maneuvers was also explored by Leung et al [9], using 2D simulations. They considered a Re = 1000 and gust ratios G = V/U ∞ = 0.27 and 0.57, for different durations of the gust.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow perturbations in unsteady environments are highly variable, so researchers often consider canonical configurations to characterize the different contributions to the aerodynamic response of the wing. One recent example of the use of canonical configurations is the work of Leung et al [4] who modelled transverse gusts using different airfoil motions: pitching, plunging and surging. Another example is the work of Mulleners et al [5] as well as Granlund et al.…”
Section: Introductionmentioning
confidence: 99%
“…The shed vorticity is subsequently assumed to convect with the freestream velocity, and does not dissipate or translate in a direction transverse to the flow. While these assumptions required for application of classical unsteady aerodynamic theory are quite strong, it continues to be successfully applied across a range of applications, such as in the modeling and regulation of lift during gust encounters [31,24,49,3], and for estimating the circulation of vortices produced by vertical gust generators [23]. At the core of classical unsteady aerodynamic theory are a small number of related functions that describe the response of the flow, and particularly the lift and moment on the airfoil, to unsteady conditions.…”
Section: Introductionmentioning
confidence: 99%